2011
DOI: 10.1007/s10549-011-1702-0
|View full text |Cite
|
Sign up to set email alerts
|

Traditional breast cancer risk factors in relation to molecular subtypes of breast cancer

Abstract: Background At least four major categories of invasive breast cancer have been reproducibly identified by gene expression profiling: luminal A, luminal B, HER2-type and basal-like. These subtypes have been shown to differ in their outcome and response to treatment. Whether this heterogeneity reflects the evolution of these subtypes through distinct etiologic pathways has not been clearly defined. Methods We evaluated the association between traditional breast cancer risk factors and risk of previously defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
207
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(227 citation statements)
references
References 25 publications
16
207
0
4
Order By: Relevance
“…These subtypes differ in terms of clinical presentation, risk factors, response to chemotherapy and radiotherapy, and patient's survival rate. [15][16][17] So microscopic subtyping and four main molecular subtyping are now a day is generally done in all newly diagnosed breast cancer. In our study after the diagnosis of breast cancer we referred the patients to higher centre for molecular subtyping and further treatment.…”
Section: Malignant Tumorsmentioning
confidence: 99%
“…These subtypes differ in terms of clinical presentation, risk factors, response to chemotherapy and radiotherapy, and patient's survival rate. [15][16][17] So microscopic subtyping and four main molecular subtyping are now a day is generally done in all newly diagnosed breast cancer. In our study after the diagnosis of breast cancer we referred the patients to higher centre for molecular subtyping and further treatment.…”
Section: Malignant Tumorsmentioning
confidence: 99%
“…3,8 This requires establishing a new approach with a more rational, comprehensive breast cancer classification system based on the three key molecules to understand further the heterogeneity of the disease in individual patients. 1 Two aspects should be considered in this new prediction system.…”
mentioning
confidence: 99%
“…15,16 This latter evaluation showed that a history of breastfeeding was inversely related to basal-like breast cancer. 16 The cohort has also been a rich source of evidence on adiposity in childhood and its relationship to subsequent risk of breast cancer, where it is inversely related to oestrogen receptor-negative breast cancer. 17 Studies of survivorship after cancer diagnosis and treatment were also an early addition to the ongoing cohort study.…”
Section: Expanding the Scopementioning
confidence: 97%